Equity – the Bottleneck and the Opportunity - Rice, Jake (Frontiers in Ecology and Evolution, 2021)
There is a widespread tendency for diverse uses of Nature, on scales from small and local to very large, to become unsustainable. Once unsustainable, bringing a use back to sustainability and keeping it sustainable then takes substantial effort and tools appropriate to the context of the use. This Perspective first asks why is the tendency for unsustainability so pervasive, when it is outcome that no user group has adopted as an objective, and ways to keep uses sustainable are known. I argue and present evidence that the common factor underlying the pervasiveness of unsustainable uses of Nature is inequity in the distribution of the benefits created from those uses, with both the wealthy “winners” of the distributional inequities and those disadvantaged and in poverty driving uses towards increasing unsustainability. Unless the inequity of distribution of benefits from uses of Nature is addressed as an issue in its own right, there are few or no pathways to medium or long-term sustainable use. However if inequity is addressed effectively, many pathways are available and societies can select the pathways appropriate to their cultural and ecological contexts.